THE INFLUENCE OF LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE PEUDADA SUBDISTRICT OFFICE, BIREUEN REGENCY - Ria Amalia; Rosmalia; Ratna Sari; Putri Ramazani; Mai Simahatie (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This research aims to determine the influence of leadership and work motivation on employee performance at the Peudada Subdistrict Office, Bireuen Regency. The population in this study consists of 44 employees, with a sample selected using purposive sampling. The data analysis method used in this research is multiple linear regression analysis, utilizing SPSS version 25 and Microsoft Excel 2014. Based on the research results, it is found that, partially, the leadership variable has a positive and significant effect on employee performance at the Peudada Subdistrict Office, Bireuen Regency. This is evidenced by the tvalue (3.047) > t-table (1.682) and a significance value of 0.004, which is less than 0.05. The motivation variable also has a positive and significant effect on employee performance at the Peudada Subdistrict Office, Bireuen Regency. This is evidenced by the t-value (2.658) > ttable (1.682) and a significance value of 0.011, which is less than 0.05. Simultaneously, leadership and work motivation have a positive and significant effect on employee performance at the Peudada Subdistrict Office, Bireuen Regency. This is evidenced by the Fvalue (59.959) > F-table (3.23) and a significance value of 0.000, which is far less than α (0.05).